Pemberdayaan Ekonomi Buah Durian Montong di Desa Karang Patihan (Pulung) - Lintang Kirana Nurhayati; Ibnu Muchlis (Social Science Academic, 2023)
This Community Service Lecture aims to apply interdisciplinary knowledge so as to be able to add knowledge while increasing student skills in developing potential in the Karang Patihan (Pulung) Village community, namely raising the potential of durian fruit for KPM students at the Islamic Institute of Sunan Giri Ponorogo. Durian fruit especially in terms of increasing production and marketing. Durian fruit and durian fruit tree seeds are traded online through the WhatsApp application through the status of Mrs. Sri's child. From there, Sri's mother's sales were selling well and selling well because her child was trying to upload them on WA status so who knows they're selling well. Alhamdulilah selling and orders increased rapidly.